Natural polysaccharide-assisted MXene porous film electrode and preparation method thereof

By combining with natural polysaccharides and introducing metal ion doping and vacuum suction filtration membrane formation technology, the problem of MXene materials stacking in hydration and electrolyte environments is solved, significantly improving its electrochemical performance and operability.

CN119447156BActive Publication Date: 2025-04-15SHANDONG UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510034472.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-15
Estimated Expiration
2045-01-09

AI Technical Summary

Technical Problem

MXene materials are prone to single-layer nanosheet stacking and aggregation in hydrated and electrolyte environments, resulting in a degradation of their performance, including reduced specific surface area, suppressed ion adsorption and diffusion, increased ion transport resistance and reduced contact area between electrodes and electrolytes.

Method used

By compounding with natural polysaccharides, using a single layer of MXene as the base material, interacting with natural polysaccharides, improving the dispersion and stability of MXene, preventing stacking, and introducing metal ion doping and vacuum suction filtration membrane formation technology to optimize the electrode structure.

Benefits of technology

Effectively prevent the stacking of MXene nanosheets, improve the performance and operability of the film, and improve electrochemical performance, including improved specific capacitance, enhanced flexibility and optimized pore structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447156B_ABST
    Figure CN119447156B_ABST
Patent Text Reader

Abstract

The present invention discloses a natural polysaccharide-assisted MXene porous film electrode and a preparation method thereof, and relates to the field of electrode technology. The technical scheme is: using hydrochloric acid and lithium fluoride to etch and intercalate MAX raw materials to obtain a MXene dispersion; mixing the MXene dispersion with a metal ion solution to obtain a metal ion-doped MXene solution; mixing the metal ion-doped MXene solution with a natural polysaccharide dispersion to obtain a natural polysaccharide-modified MXene dispersion; mixing the natural polysaccharide-modified MXene dispersion with a template, vacuum filtering and vacuum drying to obtain a flexible MXene film; performing template removal treatment on the flexible MXene film to obtain a natural polysaccharide-assisted MXene porous film electrode. The present invention solves the problem of MXene material stacking and significantly improves the electrochemical performance of the natural polysaccharide-assisted MXene porous film electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrode technology, and in particular to a natural polysaccharide-assisted MXene porous film electrode and a preparation method thereof. Background Art

[0002] With the rapid advancement of lithium battery technology, the demand for high-performance electrode materials has become increasingly urgent. In this context, MXene materials, an emerging two-dimensional transition metal carbide / nitride, have attracted much attention due to their unique physical and chemical properties. MXene materials have high conductivity and can quickly transmit electrons, reducing energy loss; at the same time, their large specific surface area provides more active sites, which is conducive to the adsorption and storage of electrolyte ions. In addition, MXene materials also exhibit excellent electrochemical properties, including high capacity, good cycle stability and rate performance. Its diverse surface chemical properties also provide possibilities for further functional modification and performance optimization.

[0003] However, despite the many theoretical advantages of MXene materials, their performance is often affected to a certain extent in practical applications, especially in hydration and electrolyte environments. Specifically, MXene materials are prone to single-layer nanosheet stacking and aggregation. The main reason for this phenomenon is the strong interaction forces between MXene nanosheets, such as van der Waals forces, which make adjacent MXene nanosheets tend to approach each other and stack together.

[0004] This stacking phenomenon has an adverse effect on the performance of MXene materials. First, stacking will significantly reduce the specific surface area of ​​MXene materials and reduce the active sites available for electrolyte ion adsorption and storage. Second, stacking will inhibit the effective adsorption and diffusion of electrolyte ions on the surface of the material, hinder the ion transmission path, and increase the ion transmission resistance. In addition, stacking will limit the contact area between the electrolyte and the electrode material, reduce the interaction between the electrolyte and the electrode material, and thus affect the electrochemical performance of the electrode.

[0005] Therefore, how to inhibit the stacking and aggregation of MXene nanosheets to fully exert their potential performance is a problem that needs to be solved at present. Summary of the invention

[0006] The technical problem to be solved by the present invention is: to overcome the shortcomings of the prior art and provide a natural polysaccharide-assisted MXene porous thin film electrode and a preparation method thereof, which not only solves the MXene material stacking problem, but also significantly improves the electrochemical performance of the natural polysaccharide-assisted MXene porous thin film electrode.

[0007] The technical solution of the present invention is:

[0008] In one aspect, the present invention provides a method for preparing a natural polysaccharide-assisted MXene porous film electrode, comprising the following steps:

[0009] S1 uses hydrochloric acid and lithium fluoride (LiF) to etch and intercalate the MAX raw material to obtain a MXene dispersion;

[0010] S2: mixing the MXene dispersion with the metal ion solution to obtain a metal ion-doped MXene solution;

[0011] S3: mixing the metal ion-doped MXene solution with the natural polysaccharide dispersion to obtain a natural polysaccharide-modified MXene dispersion;

[0012] S4: mixing the natural polysaccharide modified MXene dispersion with the template, vacuum filtering and vacuum drying to obtain a flexible MXene film;

[0013] S5 performs template removal treatment on the obtained flexible MXene film to obtain a natural polysaccharide-assisted MXene porous film electrode.

[0014] Preferably, the specific operation of step S1 is: adding lithium fluoride to a 12M hydrochloric acid solution, stirring and then adding Ti 3 AlC 2 The obtained mixed solution is stirred and then centrifuged until the pH value of the mixed solution reaches 6-7; the obtained product is further added to deionized water, ultrasonically treated in an ice bath and then centrifuged to obtain a MXene dispersion; wherein lithium fluoride, hydrochloric acid and Ti 3 AlC 2 The mass volume ratio is (1.2-1.5g):(20-30mL):(1-1.5g).

[0015] Preferably, in step S2, the metal ions are cobalt ions or nickel ions.

[0016] Preferably, in step S2, the solid content of the metal ion solution is 1-20% of the solid content of the MXene dispersion; and the concentration of the metal ion solution is 0.1-2 mg / mL.

[0017] Preferably, in step S3, the natural polysaccharide is sodium alginate.

[0018] Preferably, in step S3, the solid content of the natural polysaccharide dispersion is 1-20% of the solid content of the MXene solution after metal ion doping.

[0019] Preferably, in step S4, the template is ammonium bicarbonate or ammonium carbonate; the mass of the template is 1-20% of the solid content of the natural polysaccharide modified MXene dispersion.

[0020] Preferably, in step S5, the template removal treatment is to vacuum dry the flexible MXene film at 40-80° C. for 4-8 h.

[0021] On the other hand, the present invention provides a natural polysaccharide-assisted MXene porous thin film electrode, which is prepared by the above-mentioned method for preparing the natural polysaccharide-assisted MXene porous thin film electrode.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1. The method of preparing porous film electrodes by using natural polysaccharides to assist MXene of the present invention uses a single-layer MXene as a base material and is compounded with natural polysaccharides. Through the interaction between natural polysaccharides and MXene nanosheets, the dispersibility and stability of MXene can be effectively improved, and its stacking can be prevented, thereby improving the performance and operability of the film. In this process, natural polysaccharides play the role of "structural stabilizer", helping to maintain the single-layer nanosheet structure of MXene materials, while improving the accessibility and ion conductivity of electrolytes when forming porous films. At the same time, the present invention also introduces metal ion doping, vacuum filtration film forming and other technologies, wherein the doping of metal ions can cause the wrinkles of MXene nanosheets, so that they can better contact with the electrolyte, thereby further optimizing the structure of the electrode and improving the electrochemical performance. Finally, the present invention obtains a flexible MXene porous film electrode with excellent electrochemical performance by removing the template. This innovative method solves the problem of MXene material stacking and has broad application prospects.

[0024] 2. The present invention modifies MXene by natural polysaccharides, so that the prepared natural polysaccharide-assisted MXene porous thin film electrode has excellent flexibility while maintaining good electrical conductivity.

[0025] 3. The present invention combines vacuum filtration technology with the template method to efficiently control the pore structure and thickness of the film, thereby adjusting its macrostructure and obtaining a MXene porous film electrode with ideal porosity and surface active sites.

[0026] 4. The preparation method of the present invention is simple and easy, and the process conditions are mild, which is suitable for large-scale industrial production. At the same time, the present invention uses natural polysaccharides as auxiliary materials, which is not only environmentally friendly but also has a low production cost and strong market competitiveness. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is the electrochemical charge and discharge (GCD) diagram of the thin film electrodes prepared in Examples 1-3 of the present invention and Comparative Examples 1-3.

[0028] Figure 2It is an electrochemical cyclic voltammetry (CV) curve diagram of the thin film electrodes prepared in Examples 1-3 of the present invention and Comparative Examples 1-3.

[0029] Figure 3 This is a SEM image of the natural polysaccharide-assisted MXene porous film electrode prepared in Example 1 of the present invention.

[0030] Figure 4 This is a SEM image of the natural polysaccharide-assisted MXene porous film electrode prepared in Example 2 of the present invention.

[0031] Figure 5 This is a SEM image of the natural polysaccharide-assisted MXene porous film electrode prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0032] In order to enable persons skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.

[0033] Example 1

[0034] The method for preparing the natural polysaccharide-assisted MXene porous film electrode of this embodiment comprises the following steps:

[0035] S1 Add 1.3 g of LiF to 25 mL of 12 M HCl solution, stir for 7 min, then add 1.4 g of Ti 3 AlC 2 The obtained mixed solution was stirred at 35°C for 24h, and then centrifuged at 3500rpm for 10min, and repeated 5 times until the pH value of the solution reached 6; the obtained product was further added to deionized water, ultrasonically treated in an ice bath for 2h, and finally centrifuged at 3500rpm for 30min to obtain a 5mg / mL MXene dispersion;

[0036] S2: 4 mL of MXene dispersion is taken and mixed with 2 mg / mL of cobalt chloride aqueous solution to obtain a cobalt ion-doped MXene solution, wherein the solid content of the cobalt chloride aqueous solution is 5% of the solid content of the MXene dispersion;

[0037] S3: mixing the cobalt ion-doped MXene solution with the sodium alginate aqueous dispersion to obtain a sodium alginate-modified MXene dispersion, wherein the solid content of the sodium alginate aqueous dispersion is 15% of the solid content of the cobalt ion-doped MXene solution;

[0038] S4 further mixes the sodium alginate modified MXene dispersion with ammonium bicarbonate, treats it by vacuum filtration, and dries it under vacuum conditions to obtain a flexible MXene film, wherein the mass of ammonium bicarbonate is 15% of the solid content of the sodium alginate modified MXene dispersion;

[0039] S5 vacuum-dry the flexible MXene film at 50 °C for 5 h to remove the ammonium bicarbonate and obtain a natural polysaccharide-assisted MXene porous film electrode.

[0040] Example 2

[0041] The method for preparing the natural polysaccharide-assisted MXene porous film electrode of this embodiment comprises the following steps:

[0042] S1 Add 1.2 g of LiF to 20 mL of 12 M HCl solution, stir for 7 min, then add 1 g of Ti 3 AlC 2 The obtained mixed solution was stirred at 35 °C for 24 h, and then centrifuged at 3500 rpm for 10 min, and repeated 5 times until the pH value of the solution reached 7; the obtained product was further added to deionized water, ultrasonically treated in an ice bath for 2 h, and finally centrifuged at 3500 rpm for 30 min to obtain a 5 mg / mL MXene dispersion;

[0043] S2: 4 mL of MXene dispersion is taken and mixed with 1 mg / mL nickel chloride aqueous solution to obtain a nickel ion-doped MXene solution, wherein the solid content of the nickel chloride aqueous solution is 20% of the solid content of the MXene dispersion;

[0044] S3: mixing the nickel ion-doped MXene solution with the sodium alginate aqueous dispersion to obtain a sodium alginate-modified MXene dispersion, wherein the solid content of the sodium alginate aqueous dispersion is 1% of the solid content of the nickel ion-doped MXene solution;

[0045] S4 further mixes the sodium alginate modified MXene dispersion with ammonium carbonate, treats it by vacuum filtration, and dries it under vacuum conditions to obtain a flexible MXene film, wherein the mass of ammonium carbonate is 20% of the solid content of the sodium alginate modified MXene dispersion;

[0046] S5 vacuum-dry the flexible MXene film at 40 °C for 8 h to remove ammonium carbonate and obtain a natural polysaccharide-assisted MXene porous film electrode.

[0047] Example 3

[0048] The method for preparing the natural polysaccharide-assisted MXene porous film electrode of this embodiment comprises the following steps:

[0049] S1 Add 1.5 g of LiF to 30 mL of 9 M HCl solution, stir for 7 min, then add 1.5 g of Ti 3 AlC 2 The obtained mixed solution was stirred at 35°C for 24h, and then centrifuged at 3500rpm for 10min, and repeated 5 times until the pH value of the solution reached 6; the obtained product was further added to deionized water, ultrasonically treated in an ice bath for 2h, and finally centrifuged at 3500rpm for 30min to obtain a 5mg / mL MXene dispersion;

[0050] S2: Take 4 mL of MXene dispersion and mix it with 0.1 mg / mL nickel chloride to obtain a nickel-ion-doped MXene solution, wherein the solid content of the nickel chloride aqueous solution is 1% of the solid content of the MXene dispersion;

[0051] S3: mixing the nickel ion-doped MXene solution with the sodium alginate aqueous dispersion to obtain a sodium alginate-modified MXene dispersion, wherein the solid content of the sodium alginate aqueous dispersion is 20% of the solid content of the nickel ion-doped MXene solution;

[0052] S4 further mixes the sodium alginate modified MXene dispersion with ammonium bicarbonate, treats it by vacuum filtration, and dries it under vacuum conditions to obtain a flexible MXene film, wherein the mass of ammonium bicarbonate is 1% of the solid content of the sodium alginate modified MXene dispersion;

[0053] S5 vacuum-dry the flexible MXene film at 80 °C for 4 h to remove the ammonium bicarbonate and obtain a natural polysaccharide-assisted MXene porous film electrode.

[0054] The SEM images of the natural polysaccharide-assisted MXene porous film electrodes prepared in Examples 1-3 are as follows: Figure 3-5 As shown, it can be seen that the surface of the natural polysaccharide-assisted MXene porous film electrode prepared in Examples 1-3 exhibits a microscopic pore structure, and the presence of the pores provides a larger specific surface area, which helps the film electrode to better adsorb ions, thereby improving its capacitance performance; in addition, the pores can also increase the contact area between the electrolyte and the film electrode, reduce the ion diffusion path, and improve the ion transmission efficiency.

[0055] Comparative Example 1

[0056] The preparation method of the MXene thin film electrode of Comparative Example 1 comprises the following steps:

[0057] S1 is the same as Example 1, and a 5 mg / mL MXene dispersion is obtained;

[0058] S2 takes 4 mL of MXene dispersion, performs vacuum filtration, and then puts it into a vacuum drying oven for drying at a temperature of 35 °C and a drying time of 4 h to obtain a MXene thin film electrode.

[0059] Comparative Example 2

[0060] The preparation method of the natural polysaccharide modified MXene thin film electrode of Comparative Example 2 comprises the following steps:

[0061] S1 is the same as Example 1, and a 5 mg / mL MXene dispersion is obtained;

[0062] S2: 4 mL of MXene dispersion is taken and mixed with sodium alginate aqueous dispersion to obtain sodium alginate modified MXene dispersion, wherein the solid content of the sodium alginate aqueous dispersion is 15% of the solid content of the MXene dispersion;

[0063] S3 vacuum-filters the sodium alginate-modified MXene dispersion, and then vacuum-dries it at 50°C for 4 hours to obtain a natural polysaccharide-modified MXene thin film electrode.

[0064] Comparative Example 3

[0065] The method for preparing the natural polysaccharide-assisted MXene porous film electrode of Comparative Example 3 comprises the following steps:

[0066] S1 is the same as Example 1, and a 5 mg / mL MXene dispersion is obtained;

[0067] S2: 4 mL of MXene dispersion is taken and mixed with sodium alginate aqueous dispersion to obtain sodium alginate modified MXene dispersion, wherein the solid content of the sodium alginate aqueous dispersion is 15% of the solid content of the MXene dispersion;

[0068] S3 further mixes the sodium alginate modified MXene dispersion with ammonium bicarbonate, treats it by vacuum filtration, and dries it under vacuum conditions to obtain a flexible MXene film, wherein the mass of ammonium bicarbonate is 15% of the solid content of the sodium alginate modified MXene dispersion;

[0069] S4 vacuum dried the flexible MXene film at 50 °C for 5 h to remove the ammonium bicarbonate and obtain a natural polysaccharide-assisted MXene porous film electrode.

[0070] The electrochemical performance of the thin film electrodes prepared in Examples 1-3 and Comparative Examples 1-3 was tested, and the electrochemical charge and discharge test results were as follows: Figure 1 As shown in Table 1, the test conditions are a three-electrode system, with the thin film electrode as the working electrode, the platinum electrode as the counter electrode, silver chloride as the reference electrode, and the test electrolyte being 3M sulfuric acid electrolyte.

[0071] Depend on Figure 1 It can be seen that by comparing Comparative Example 1 with Comparative Example 2, the natural polysaccharide increases the MXene interlayer spacing, thereby improving the mass specific capacitance of the prepared thin film electrode. Comparing Comparative Example 2 with Comparative Example 3, the removal of the template helps to form a porous structure of the thin film electrode, which can provide more ion diffusion space and help improve the mass specific capacitance of the thin film electrode. Comparing Comparative Example 3 with Example 1, the introduction of metal ions can enable MXene nanosheets to provide more effective electrochemical active sites, thereby further enhancing the electrochemical performance of the thin film electrode.

[0072] Table 1 Test results of mass specific capacitance of thin film electrodes prepared in Examples 1-3 and Comparative Examples 1-3

[0073]

[0074] As can be seen from Table 1, compared with Comparative Examples 1-3, the natural polysaccharide-assisted MXene porous film electrodes prepared in Examples 1-3 have a higher mass specific capacitance. At a current density of 1A / g, the mass specific capacitance of the natural polysaccharide-assisted MXene porous film electrodes prepared in the present invention can reach up to 581F / g, which is much higher than the film electrodes of Comparative Examples 1-3. This is because the natural polysaccharide-assisted MXene porous film electrodes prepared in the present invention exhibit a larger specific surface area and higher conductivity in terms of surface structure and porosity, which provides more paths and spaces for ion diffusion, thereby enabling it to have a higher mass specific capacitance. In addition, the porous structure of the natural polysaccharide-assisted MXene porous film electrodes prepared in the present invention helps to enhance the permeability of electrolyte ions in the electrode, thereby reducing the internal resistance, improving the ion adsorption capacity and reaction rate of the electrode, reducing the volume change during the charge and discharge process, reducing the increase in internal resistance, and further improving the electrochemical performance of the film electrode.

[0075] The electrochemical cyclic voltammetry (CV) curves of the thin film electrodes prepared in Examples 1-3 and Comparative Examples 1-3 are as follows: Figure 2 As shown by Figure 2 It can be seen that Example 1 optimizes the structure, conductivity, ion diffusion channels and electrochemical active sites of the thin film electrode through the synergistic effect of metal ions and natural polysaccharides, thereby significantly improving the electrochemical performance.

[0076] In summary, compared with Comparative Examples 1-3, the electrochemical performance of the natural polysaccharide-assisted MXene porous film electrodes prepared in Examples 1-3 is significantly improved.

Claims

1. A method for preparing a natural polysaccharide-assisted MXene porous film electrode, characterized in that: The following steps are involved: S1 uses hydrochloric acid and lithium fluoride to etch and intercalate the MAX raw material to obtain a MXene dispersion; S2: mixing the MXene dispersion with the metal ion solution to obtain a metal ion-doped MXene solution; S3: mixing the metal ion-doped MXene solution with the natural polysaccharide dispersion to obtain a natural polysaccharide-modified MXene dispersion; S4: mixing the natural polysaccharide modified MXene dispersion with the template, vacuum filtering and vacuum drying to obtain a flexible MXene film; S5: performing template removal treatment on the obtained flexible MXene film to obtain a natural polysaccharide-assisted MXene porous film electrode; In step S2, the metal ion is a cobalt ion or a nickel ion; In step S3, the natural polysaccharide is sodium alginate; In step S4, the template is ammonium bicarbonate or ammonium carbonate.

2. The method for preparing a natural polysaccharide-assisted MXene porous film electrode according to claim 1, characterized in that: The specific operation of step S1 is: adding lithium fluoride to a 12M hydrochloric acid solution, adding Ti3AlC2 after stirring, stirring the obtained mixed solution and centrifuging it until the pH value of the mixed solution reaches 6-7; further adding the obtained product into deionized water, ultrasonically treating it in an ice bath and centrifuging it to obtain a MXene dispersion; wherein the mass volume ratio of lithium fluoride, hydrochloric acid and Ti3AlC2 is (1.2-1.5g): (20-30mL): (1-1.5g).

3. The method for preparing a natural polysaccharide-assisted MXene porous film electrode according to claim 1, characterized in that: In step S2, the solid content of the metal ion solution is 1-20% of the solid content of the MXene dispersion; the concentration of the metal ion solution is 0.1-2 mg / mL.

4. The method for preparing a natural polysaccharide-assisted MXene porous film electrode according to claim 1, characterized in that: In step S3, the solid content of the natural polysaccharide dispersion is 1-20% of the solid content of the MXene solution after metal ion doping.

5. The method for preparing a natural polysaccharide-assisted MXene porous film electrode according to claim 1, characterized in that: In step S4, the mass of the template is 1-20% of the solid content of the natural polysaccharide modified MXene dispersion.

6. The method for preparing a natural polysaccharide-assisted MXene porous film electrode according to claim 1, characterized in that: In step S5, the template removal treatment is to vacuum dry the flexible MXene film at 40-80° C. for 4-8 hours.

7. Natural polysaccharide-assisted MXene porous film electrode, characterized in that: The method is described in any one of claims 1 to 6 to prepare a natural polysaccharide-assisted MXene porous film electrode.

Citation Information

Patent Citations

  • Flexible self-supporting MXene quantum dot / MXene film electrode and preparation method and application thereof

    CN115188606A

  • MXene-alginate negative electrode material, preparation method and lithium ion battery

    CN117199362A